EL RECURSO DE LA INVENTIO EN LA ADAPTACIÓN CINEMATOGRÁFICA DEL LAZARILLO DE TORMES - Pedro Jesús MORICHE HERMOSO (Fonseca, Journal of Communication, 2023)
In this article it is highlighted the importance of one of the many resources that filmmakers use when shown the screen version: la inventio. La inventio is a resort classed as expansion. To see its effectiveness and multiple purposes, it is used the anonymous work of the 16th century, El Lazarillo de Tormes, as model, and the adaptations done by Fernando Fernán Gómez at the beginning of 21st century.